Genre and Attitude to develop Characterization of Protagonist’s Heroes in Narrative Asset of Mobile Legend: Bang-bang - Wijaya, Rahmaditya Khadifa Abdul Rozzaq; Wardhani, Evi Murti; Kamaluddin, Ahnaf Dzaky; Bataiv, Misbah Faturrahman (PT FORMOSA CENDEKIA GLOBAL, 2025)
MOBA games contain highly intriguing narrative assets that are worth exploring. In the MOBA game Mobile Legends, narrative assets are found in the Mastery Code menu. Interestingly, these narrative assets are not always structured as traditional narratives; they can also appear in other textual genres. The aim of this research is to describe how genre functions as a supporting element in the characterization of the hero protagonist. Additionally, this study analyzes the Attitude System, a tool within the Appraisal framework, to understand how it contributes to the characterization of the hero protagonist. This research adopts a qualitative, descriptive approach, as it aims to naturally describe the observed phenomena.